2012
DOI: 10.1182/blood-2011-12-399030
|View full text |Cite
|
Sign up to set email alerts
|

S1PR1 is an effective target to block STAT3 signaling in activated B cell–like diffuse large B-cell lymphoma

Abstract: STAT3 plays a crucial role in promoting progression of human cancers, including several types of B-cell lymphoma. However, as a transcription factor lacking its own enzymatic activity, STAT3 remains difficult to target with small-molecule drugs in the clinic. Here we demonstrate that persistent activated STAT3 colocalizes with elevated expression of S1PR1, a G-protein-coupled receptor for sphingosine-1-phosphate (S1P), in the tumor cells of the activated B cell-like subtype of diffuse large B-cell lymphoma pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 41 publications
7
77
0
3
Order By: Relevance
“…This finding is consistent with the observation of others that S1P and STAT3 signaling is linked in a coactivating pathway, in which S1P acts through S1PR1 to activate JAK2/STAT3. STAT3 is a transcriptional activator of IL-6 and S1PR1 (15,40). Whereas the prior studies used artificial expression systems to demonstrate this interaction, we have found that treatment of WT MEFs promotes JAK2 activation in a manner that requires S1P export via SPNS2 and extracellular S1PR1 signaling.…”
Section: Discussionmentioning
confidence: 63%
“…This finding is consistent with the observation of others that S1P and STAT3 signaling is linked in a coactivating pathway, in which S1P acts through S1PR1 to activate JAK2/STAT3. STAT3 is a transcriptional activator of IL-6 and S1PR1 (15,40). Whereas the prior studies used artificial expression systems to demonstrate this interaction, we have found that treatment of WT MEFs promotes JAK2 activation in a manner that requires S1P export via SPNS2 and extracellular S1PR1 signaling.…”
Section: Discussionmentioning
confidence: 63%
“…It is of great importance to progression ( 81 ). This S1PR1-STAT3 axis also plays an important role in lymphomas ( 82 ) and is crucial for myeloid cell colonization at future metastatic sites in prostate and melanoma cancers ( 83 ). We have recently extended these observations and shown that S1P produced by upregulation of SphK1 during colitis and associated cancer is essential for production of the multifunctional NF-kB-regulated cytokine IL-6, persistent activation of the transcription factor STAT3, and consequent upregulation of the S1PR, S1PR1.…”
Section: Discussionmentioning
confidence: 99%
“…AKT and Bcl-associated death promoter pro-survival pathways were also reduced by FTY720 administration to neuroblastoma cells in an in vitro and an in vivo xenograft model, resulting in decreased cancer cell viability ( 175 ). S1PR expression in several hematological malignancies has also been described, including S1P 1 expression by classical Hodgkin's lymphoma (CHL) cells, B cell chronic lymphocytic leukemia (B-CLL) cells, and activated B celllike DLBCL cells (176)(177)(178). Chronic myeloid leukemia (CML) cells expressed S1P 2 , which resulted in increased stability of the B cell receptor-Abl1 fusion protein and subsequently, increased proliferation ( 179 …”
Section: Nervous Systemmentioning
confidence: 99%